Exploring the diversity of galls on Artemisia indica induced by Rhopalomyia species through morphological and transcriptome analyses - Seiji Takeda; Makiko Yoza; Sawako Ueda; Sakura Takeuchi; Akiteru Maeno; Tomoaki Sakamoto; Seisuke Kimura (Plant Direct)
Abstract Plant galls generated by insects have highly organized structures, providing nutrients and shelter to the insects living within them. Most research on the physiological and molecular mechanisms of gall development has focused on single galls. To understand the diversity of gall development, we examined five galls with different morphologies generated by distinct species of Rhopalomyia (gall midge; Diptera: Cecidomyiidae) on a single host plant of Artemisia indica var. maximowiczii (Asteraceae). Vasculature developed de novo within the galls, indicating active transport of nutrients between galls and the host plant. Each gall had a different pattern of vasculature and lignification, probably due to differences in the site of gall generation and the gall midge species. Transcriptome analysis indicated that photosynthetic and cell wall–related genes were down‐regulated in leaf and stem galls, respectively, compared with control leaf and stem tissues, whereas genes involved in floral organ development were up‐regulated in all types of galls, indicating that transformation from source to sink organs occurs during gall development. Our results help to understand the diversity of galls on a single herbaceous host plant.